If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3 + 2x) = -4x + 2 (3 * 6 + 2x * 6) = -4x + 2 (18 + 12x) = -4x + 2 Reorder the terms: 18 + 12x = 2 + -4x Solving 18 + 12x = 2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 18 + 12x + 4x = 2 + -4x + 4x Combine like terms: 12x + 4x = 16x 18 + 16x = 2 + -4x + 4x Combine like terms: -4x + 4x = 0 18 + 16x = 2 + 0 18 + 16x = 2 Add '-18' to each side of the equation. 18 + -18 + 16x = 2 + -18 Combine like terms: 18 + -18 = 0 0 + 16x = 2 + -18 16x = 2 + -18 Combine like terms: 2 + -18 = -16 16x = -16 Divide each side by '16'. x = -1 Simplifying x = -1
| 6x^2+11x-5=0 | | 169-4x=41x+24 | | 12-10x=132-38 | | 0.6x-6=9 | | 3+2x*6=x*(-4)+2 | | y-(-3)=10(x-5) | | 3x+11=-5-7x | | 3+3x*6=x*(-4)+2 | | 2x+3*6=x*-4+2 | | 60v^2-117vd+54d^2= | | 204-2x=43x+19 | | 222-3x=42x+17 | | x+x+10=100 | | 3a^2-18a=0 | | 2x+3(6x-15)=-145 | | -2x^2-14x+30=0 | | -4x^2-7x=-5 | | 6-6x=2x+5 | | 17+2x+x=74 | | 10x^2+60x=-50 | | 8(1)a+4(1)a+8(1)ab= | | -(4y+8)-(3y-5)=-1 | | 1-x+5=8 | | 4u(5u+3)=0 | | 58-3x=15x+20 | | 10x+5=7x-4 | | H=30-16t^2 | | -x-7(15)=x-2(3) | | 3c+4=20-c | | -13-10x=7x+21 | | -5x-5(-3x-8)=160 | | 2n^2-n=0 |